Devi Shakta cult: Pahari miniature painting - "Rahi, Onkar" (New Delhi, 2008)
The Devi Mahatamya in pictorial detail in this volume is a study of Devi Shakti-the supreme feminine deity. She is Dashamahavidya of the Bhairavas, and also Katyayini, Kalaratri and Mahagauri. As Shiva's Adishakti, she is Gayatri, the goddess of all science and knowledge.
Keywords: Pahari painting